The potency of Andrographis paniculata Nees extract to increase the viability of monocytes following exposure to Porphyromonas gingivalis - Yani Corvianindya Rahayu; Didin Erma Indahyani; Sheila Dian Pradipta; Anis Irmawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Periodontitis is a chronic infectious disease affecting the global population. In Indonesia, the prevalence of periodontal disease has reached 57.6% across all age groups. The bacterium considered as the orginator factor of periodontitis is Porphyromonas gingivalis (P. gingivalis). Herbal ingredients are currently being promoted as a form of treatment because of the minimal side effects they induce. Andrographis paniculata Nees (ApN) extract produces pharmacological effects, including ones immunomodulatory in character, rendering possible its application as a preparation for treating periodontitis. Purpose: The purpose of the study was to prove the potency of Andrographis paniculata Nees extract in increasing the viability of monocytes following exposure to P. gingivalis. Methods: The sample was divided into four groups, namely; Control negative (C-): monocytes in the medium, not exposed to P. gingivalis; Control positive (C+): monocytes in the medium, exposed to P. gingivalis; Treatment I (AP25): monocytes with 25% ApN extract, exposed to P. gingivalis; Treatment II (AP50): monocytes with 50% ApN extract, exposed with P. gingivalis. The monocytes were exposed to 100 uL P. gingivalis for 4.5 hours and stained with trypan blue. Observations were conducted using an inverted microscope at 200x magnification. The percentage of viable monocytes was calculated based on the ratio of the number of the cells which absorbed trypan blue staining to that which did not. Data was tested using a one-way ANOVA followed by an LSD test. Results: There were significant differences between the treatment groups in the number of viable monocytes (p=0.001) they contained. Monocyte viability was higher in the 25% ApN extract group than that exposed to 50% P. gingivalis. Conclusion: Andrographis paniculata Nees extract demonstrates the potency to increase monocyte viability following exposure to P. gingivalis.